Mapping Regional Inequality and Household Economic Stratification in East Nusa Tenggara Based on a Wealth Index - Aslam Muwaffiq, Muhammad; Ramadhan, Gilang; Sari Verdiana, Antokalina (Publikasi Indonesia, 2026)
Conventional monetary-based economic measurement is often biased, particularly in regions with a dominant informal sector and seasonal income fluctuations. This research aims to construct a Wealth Index in East Nusa Tenggara (NTT) Province as a more stable proxy for long-term welfare. Using microdata from the 2025 National Socio-Economic Survey (SUSENAS), the weighted principal component analysis (PCA) method was applied to 18 binary-transformed household asset variables. The analysis utilized R statistical software to ensure accurate population stratification into five welfare quintiles. Statistical validation results showed a Kaiser–Meyer–Olkin (KMO) value of 0.84 and a highly significant Bartlett’s test (p < 0.001), indicating excellent data suitability. The first principal component (PC1) was selected as the single index capable of explaining 20.84% of the total data variance. Loading factor analysis revealed that tertiary asset ownership, such as computers, air conditioners, and cars, possessed the highest discriminatory power, concentrated in Quintile 5 (richest), while households in Quintile 1 (poorest) were characterized by deprivational basic housing conditions. Spatially, an extreme center–periphery divide was identified, with welfare concentrated in urban areas such as Kupang City, while outer archipelagic regions remain underdeveloped. This study recommends asymmetric, place-based policy interventions, prioritizing basic infrastructure development in identified poverty pockets. Furthermore, the generated index is recommended as a robust proxy for modeling ability to pay in actuarial pricing and microinsurance schemes for the informal sector.